SOCIO-PSYCHOLOGICAL TRAINING AS A MEANS OF CORRECTION OF ADOLESCENTS 'COMMUNICATION WITH PEERS (Pedagogy of Higher and Secondary Education, 2022)
In article training as a way of correction that promotes personal growth of the teenager in dialogue with consemporaries is considered.
Keywords: training; training structure; dialogue with contemporaries is considered